(3eSGFd GdLfGRIs - (3EHQGgje Hf jhSa GdHhdhjs ((3ESeGYjd Hf HcQ Hf edG ESeGYjd s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg fSJYjf GdMeO ddg GdPi jbHd JhHg YHGOg MGdI GdEMJVGQ hjXgQge MGd MjGJge hHYO eeGJge HGdeGA GdHGQO hGdMGQ hHYO ajbhd GdHhdhi ahLOJ GdCfSH HGdEfJNGH hGdLeY eSGFd GdLfGRI s
(3BNQgG (B:s
(3ceG dGjZSd GdQLGd hCeG GdUHjGf aYfO CHj MfjaI QMeg Gddg JYGdi jZSdhf gPG cdg eCNhP ef GdJGJGQNGfjI hGdeMjW GdHQgGf GdMeO ddg Ydi GdJeGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3Gdabg GdESdGejs